A Study to Assess the Effectiveness of Lecture-Cum-Demonstration on Knowledge and Practice Regarding Biomedical Waste Management Among Allied Health Science Students at GIMS, Gadag - Padmaraj Walikar; Sanjiv Haralayya; Kushal B. Hebbali; Kavya Channali (International Journal of Evidence Based Nursing And Practices, 2025)
Background: Biomedical waste management is a critical aspect of healthcare practice, and inadequate knowledge and poor handling can pose serious risks to health professionals, patients, and the environment. Allied Health Science students, as future healthcare providers, must be well-versed in the principles and practices of biomedical waste management. This study aims to assess the effectiveness of a lecture-cum-demonstration program on improving knowledge and practice related to biomedical waste management among Allied Health Science students at GIMS, Gadag. Objectives: (1) To assess the baseline knowledge and practices regarding biomedical waste management among Allied Health Science students. (2) To evaluate the impact of a lecture combined with a demonstration on biomedical waste management among Allied Health Science students. (3) To examine the relationship between post-test knowledge and practice scores and selected socio-demographic variables of the students. Methodology: The study adopts an evaluative research approach with a one-group pre-test and post-test design (quasi-experimental). The source of data was Allied Health Science students enrolled at the GIMS Institute, Gadag. A structured questionnaire and observation checklist was used to collect data on students’ knowledge and practices before and after the educational intervention. Statistical Methods: Descriptive statistics such as frequency, mean, median, mode, and standard deviation was used to assess the levels of knowledge and practice regarding biomedical waste management. The paired 't'-test was employed to determine the effectiveness of the lecture-cum-demonstration intervention. Additionally, the chi-square test was used to analyze the association between post-test scores and selected socio-demographic variables. Conclusion: This study is expected to provide insight into the current awareness and practice levels of biomedical waste management among Allied Health Science students and demonstrate the effectiveness of structured educational interventions in enhancing compliance with standard waste management protocols.
Keywords: Biomedical waste management; allied health science students; educational intervention; knowledge and practice; lecture-cum-demonstration